2007
DOI: 10.1158/0008-5472.can-06-3935
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulation of Phosphoglucose Isomerase/Autocrine Motility Factor Results in Mesenchymal-to-Epithelial Transition of Human Lung Fibrosarcoma Cells

Abstract: Phosphoglucose isomerase (PGI) is one of the glycolytic enzymes and is a multifunctional enzyme that functions in glucose metabolism inside the cell while acting as a cytokine outside the cell, with properties that include autocrine motility factor (AMF) regulating tumor cell motility. Although there are many studies indicating that PGI/AMF has been implicated in progression of metastasis, no direct studies of the significance of exogenous PGI/AMF on tumor progression have been reported. Here, we report on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 38 publications
1
48
0
Order By: Relevance
“…GPI expression is induced by hypoxia [52]. Its downregulation has been described to lead to mesenchymal to epithelial transition in lung cancer cells [53]. It is tempting to speculate that induction of GPI constitutes a link between aerobic glycolysis [54] and tumor cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…GPI expression is induced by hypoxia [52]. Its downregulation has been described to lead to mesenchymal to epithelial transition in lung cancer cells [53]. It is tempting to speculate that induction of GPI constitutes a link between aerobic glycolysis [54] and tumor cell motility.…”
Section: Introductionmentioning
confidence: 99%
“…rAMF Induces Cell Migration but Not Cell Proliferation in Two Melanoma Cell Lines (SBcl-2 and 1205Lu)-AMF is critical for the migration, invasion, metastasis, and anti-apoptotic effects of malignant tumor cells, and its multiple roles in tumor progression may be mediated by certain downstream pathways and effectors (2,5,6,8,(33)(34)(35). A previous study reported that melanoma cells secrete and respond to AMF in an autocrine manner with increased motility (2).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated serum AMF is found in patients with malignant tumors such as colorectal, lung, kidney, breast and gastrointestinal carcinomas and is well correlated with the development of metastasis (Iiizumi et al, 2008). Moreover, overexpression of AMF in normal fibroblasts lead to a gain of tumorigenicity (Funasaka et al, 2007). During tumor progression, an additional role of AMF is revealed, namely, it is demonstrated that AMF not only stimulates AMF-producing tumor cell motility in an autocrine manner by binding to its receptor, but also acts as a paracrine factor for vein endothelial cells; when functioning as a paracrine factor, AMF induces angiogenesis by stimulating cell motility and upregulating its VEGFR expression, and it may facilitate metastasis by becoming more active at the metastasis phase (Funasaka et al, 2001).…”
Section: Discussionmentioning
confidence: 99%